Understanding children's psychology through their paintings : - Trần, Thị Minh Đức (Science and Technics, 2009)
Before children have mastered the use of spoken language, it is natural that the only form of expression they have are spontaneous images. But even after children start speaking, feelings that they are unable to put in words can often be expressed more easily through drawings and paintings.